PERLINDUGAN HUKUM TERHADAP KONSUMEN DALAM PENGGUNAAN KOSMETIK KRIM PEMUTIH (RACIKAN) - Rosadi, Agus Imron (Tadulako Master Law Journal, 2021)
Legal protection is a protection given to legal subjects in accordance with the rule of law. In recent years it has increasingly demanded attention, because many events harm consumers. many cosmetic product consumers always want to look good, in various ways they want to change their appearance. Only with a few weeks or even a few days the skin will be stuck and tight. Many products still use prohibited ingredients and do not include components, registration numbers, manufacturer names, warning of side effects, expiration dates or information. 1. How Legal Protection Against Consumers Who Experience Losses Due to the Use of Whitening Cream. 2. What Factors Influence Law Enforcement on the Distribution of Harmful Cosmetics. The type of legal research used is empirical juridical study of the applicable legal provisions and what happens in reality in the community. Based on research consumers have not received adequate protection and ineffective protection of consumer law that experiences losses this consumer ignorance of what efforts he will do if experiencing losses and lack of consumer understanding of their rights and factors that affect law enforcement of circulation dangerous cosmetics, namely: Law enforcement factors that do not work effectively. Facilities or facilities factors are limited funds, experts, and laboratories. Community factors are lack of knowledge of the community about the dangers of cosmetic cosmetics and their rights, lack of socialization to the public, and people who want instantaneously without going through a long process, and cultural factors that is, consumers tend to only see the material, when they like and are sold at cheap prices they take.